Moderate-dose cyclophosphamide in the treatment of relapsed/refractory T-cell large granular lymphocytic leukemia-associated pure red cell aplasia. Issue 3 (15th March 2016) - Peng, Guangxin; Yang, Wenrui; Zhang, Li; Zhou, Kang; Li, Yang; Li, Yuan; Ye, Lei; Li, Jianping; Fan, Huihui; Song, Lin; Zhao, Xin; Wu, Zhijie; et al.
Abstract : Background : T-cell large granular lymphocyte leukemia (T-LGLL) is a rare disorder characterized by clonal proliferation of large granular lymphocytes (commonly CD3+/CD8+/CD57+). However, the available data regarding the optimal treatment for relapsed/refractory T-LGLL patients are limited. Methods : We retrospectively reviewed 10 patients treated with immunosuppressive therapy consisting of intravenous moderate-dose cyclophosphamide (MD-CTX) together with oral cyclosporine A for relapsed/refractory T-LGLL in our hospital between July 2006 and March 2013. Results : The overall response rate to MD-CTX was 60% (6/10; hematologic complete remission rate, 50%; hematologic partial remission rate, 10%). The median time to response was 28.5 days (range, 20–118 days). The relapse rate of MD-CTX was 50% (3/6); two of these three patients achieved hematologic complete remission after receiving a second course of MD-CTX. Neutropenia was the major adverse event of the MD-CTX regimen. The median time to neutropenia was 5.5 days (range, 1–10 days) and the median neutropenia duration was 5 days (range, 3–15 days). None of the patients developed severe infection. Conclusions : The MD-CTX regimen appears efficacious and safe in the treatment of relapsed/refractory T-LGLL patients.